Impact of Pharmacokinetic Parameters Modifications of Tamsulosin Hydrochloride Controlled Release Pellets - Palanisamy Vishnu (Journal of Global Pharma Technology, 2019)
In recent years scientific and technological advancements have been made in the research and development of controlled release oral drug delivery systems by overcoming physiological adversities. There are so many oral delivery systems in that one of the advance techniques is Pellatization. Tamsulosin controlled release pellets prepared by pellatization method that the Tamsulosin is coated on inert suger spheres by using non perial seeds as a binder solutions and Hydroxypropylmethylcellose, Ethyl cellose, Eudragit, Triethyl citrate coating agents used for controlled release action. The prepared pellets were evaluated for Moisture content, Acid resistance Assay, and In-vitro drug release study. All the formulation exhibited assay, Moisture content with in the range given in USP. Dissolution studies revealed that formulations containing Eudragit 0.287gms coating agent Hydroxypropylmethylcellose, 0.00312gm of ethyl cellose 0.138gm Showed 100% of drug release, at the 8th hour. The concentration of coating agents Hydroxtpropylmethycellose and Ethyl cellose had an effect on in-vitro drug release had the same drug release profile when compare with US dissolution parameters, and innovator drug release. Thus, the pellets apart from fulfilling all official and other specifications and exhibited higher rate of drug release.